Complete postoperative anuria by nephrectomy in a solitary kidney - Pazos Varela, Ricardo (1918)
In July 1917, I first saw a patient who complained of kidney pain (vertebral spinous supraintra cost-points, sub-costal Pasteau). This pain coincided with an intense febrile excitement, and such crises were repeated in the course of the past five years. From age 16, lymphatic temperament, enmagrecida and pale, was imposed as tuberculous.